The Effectiveness of Analgesics in Pain Treatment in Critically Ill Children: a Literature Review - Taufiq Kadafi, Kurniawan; Yuliarto, Saptadi; Jihan Ruhi Said, Astika; Khalasha, Takhta (Pediatric Sciences Journal, 2023)
Adequate pain management is an important and common requirement in health care in pediatric intensive care units. There are many pain assessment scales in children based on the literature, but the guidelines for using pain scales as a guide in pain management have not been widely discussed. One of the most common pain interventions is to provide opioid or non-opioid analgesics. Analgesic drugs given to critically ill children can provide different anti-pain outcomes when measured by a pain scale. Therefore, this literature review will compare the effectiveness of analgesics in pain management in critically ill children.